Characterization of the spontaneous flora under plurispecific and monospecific afforestations in zone of semi-deciduous dense forest of Côte d'Ivoire: case of the classified forest of Bouaflé - Kouassi, Kouadio henri; Djaha, Kouamé; Hervé, Kouassi Roland , (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The present study relates to the analysis and the evaluation of the spontaneous flora under various types of afforestation in the classified forest of Bouaflé in semi-deciduous dense forests zone of Côte d'Ivoire. The main aim of this study was to evaluate the richness and the diversity of the flora under various types of afforestation in order to find decision-making tools for the orientation of the future afforestation campaigns aiming to the restoration of the flora of the degraded zones of Côte d'Ivoire. The flora was characterized starting from floristic inventories realized under retimbered spaces. The methods used were that of the surface combined with that of the itinerant one. The results showed that the flora is slightly diversified under the monospecific type of afforestation except the afforestation containing Cedreala odorata and is slightly diversified under the plurispecific type of afforestation. The majority of the species inventoried under the two types of afforestation are zoochores and/or anémochores. Twenty-seven (27) species with particular status were inventoried under the afforestation of the zone of study. These species were mainly inventoried under the plurispecific afforestation.